Utilization Of Information Technology In The Field Education (E-education) - Arta Eiji; Arata Gin (Pandawan Sejahtera Indonesia, 2021)
The development of information technology makes it easy to communicate the exchange of information so that the place, time and distance are no longer an obstacle. The development of information technology so rapidly could not be separated from the development of computer engineering. Advances in computer and information technology also provides a positive impact on education. Application areas of computer technology and information technology are the most influential in the field of education is the use of computer networks and the Internet. With the internet information services to target students are not limited space, where time and distance. Through the internet information services can be provided as a source of learning, learning media can be studied according to the speed of learners. Media study is not limited to letters and pictures but can be combined with graphics, animations, video, audio together so that the media is better known as multimedia. Positive influence of Internet use for education in developing human resources education should be able to follow the development of science and technology applications. Applications include the industrial world so that graduates are able to meet the demands of the workplace competencies. Based on these facts one way to be able to follow the rapid development of science and technology is to always access the information up to date and all it can in the can over the internet. However, its implementation is still required in support of infrastructure and human resource capabilities well as providers, managers and information users.